[3 + 2] vs. [4 + 1] Annulation: revisiting mechanism studies on the phosphine-catalysed domino sequence of alkynoates and activated methylenes. Issue 21 (18th May 2022) - Chen, Yan-Shan; Zheng, Yu; Tang, Kai; Xie, Zhen-Zhen; Ye, Zhi-Peng; Li, Ming-Zhi; Chen, Kai; Xiang, Hao-Yue; Yang, Hua
Abstract : DFT studies to rationalize the reaction mechanism of the phosphine-catalyzed domino sequences of alkynoates and activated methylenes. Abstract : The mechanism of the phosphine-catalysed domino sequence of alkynoates and activated methylenes has been computationally studied. The computational results revealed that the [3 + 2] annulation sequence could be ruled out, due to a difficult Knoevenagel condensation of aromatic aldehydes and active methylenes. The reaction proceeds through a [4 + 1] annulation pathway, which involves a phosphine-catalysed MBH-type reaction followed by a [1, 5]-proton shift and dehydration to afford vinyl phosphonium intermediates as four-carbon synthons in the annulation reaction. Then 1, 3-dicarbonyls act as nucleophiles to attack vinyl phosphonium intermediates, subsequently leading to a stepwise [1, 3]-proton shift and an intramolecular nucleophilic attack to close the five-member ring.